2013
DOI: 10.1016/j.seizure.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adult patients with epilepsy and their family members

Abstract: Interventions should address both PWE and family members and focus on the self-care improvement of PWE and the well-being and coping of family members. A patient-centred approach needs to include both the PWE and the relatives and address family support in order to alleviate stress in the patients and relatives alike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 58 publications
8
51
0
1
Order By: Relevance
“…Concerning the attitude of the families in face of epilepsy, the participants of this study reported feeling protected; distancing and withdrawal of relatives; feeling as a burden to their family. In relation to this aspect, other studies (19,20) have presented results similar to those of this research. Aiming to analyze patient perceptions about epilepsy and family support and their correlation with QoL, such studies showed that participants believed that family members offered them understanding and compassion (19,20) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Concerning the attitude of the families in face of epilepsy, the participants of this study reported feeling protected; distancing and withdrawal of relatives; feeling as a burden to their family. In relation to this aspect, other studies (19,20) have presented results similar to those of this research. Aiming to analyze patient perceptions about epilepsy and family support and their correlation with QoL, such studies showed that participants believed that family members offered them understanding and compassion (19,20) .…”
Section: Discussionsupporting
confidence: 89%
“…In relation to this aspect, other studies (19,20) have presented results similar to those of this research. Aiming to analyze patient perceptions about epilepsy and family support and their correlation with QoL, such studies showed that participants believed that family members offered them understanding and compassion (19,20) . The findings of these studies also revealed that EIs reported a constant feeling of being different, devalued, and a nuisance to their relatives (19,20) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Somatic and psychological health, emotional health, quality of life, and well-being have all been shown to deteriorate among caregivers of those with epilepsy [2,4]. The negative impact of caring for a loved one with epilepsy on family members is widespread and has been seen across a variety of cultures [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Mehrer-Imhof et al indicated that patients' quality of life depended on the quality of life of their family members, as their caregivers (10). Habibzade et al, in their study, revealed that 52% of caregivers had moderate and low quality of life and more that 60% of them were partly unsatisfied with the level of care they provided for them-selves.…”
Section: Introductionmentioning
confidence: 99%